2009
DOI: 10.1017/s0043933909000026
|View full text |Cite
|
Sign up to set email alerts
|

The potential of cassava products in diets for poultry

Abstract: Inadequate supply, exorbitant prices and diversion towards using cereal grains for biofuel production, particularly maize, has led to a constant search for alternative energy sources for poultry and other non-ruminant species. The abundant availability of cassava in certain regions makes it a good alternative to maize and other cereal grains. Cassava root meal is rich in carbohydrate but low in protein and all other nutrients, whereas, cassava leaf meal is a moderate source of protein. Results of studies to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 34 publications
(21 reference statements)
3
44
2
3
Order By: Relevance
“…The protein content of CRM used in the present study is higher than the 2.8% (Buitrago & Luckett 1999) and 3.6% (Chauynarong et al 2009;Uchegbu et al 2011) reported. Factors such as cultivar, conditions of the soil and stage of maturity, which have all been reported to affect the composition of cassava products (Ravindran & Ravindran 1988;Agwunobi & Okeke 2000) may be reasons for the higher protein content observed in the present study compared to values in literature.…”
Section: Resultscontrasting
confidence: 65%
“…The protein content of CRM used in the present study is higher than the 2.8% (Buitrago & Luckett 1999) and 3.6% (Chauynarong et al 2009;Uchegbu et al 2011) reported. Factors such as cultivar, conditions of the soil and stage of maturity, which have all been reported to affect the composition of cassava products (Ravindran & Ravindran 1988;Agwunobi & Okeke 2000) may be reasons for the higher protein content observed in the present study compared to values in literature.…”
Section: Resultscontrasting
confidence: 65%
“…The crude protein content of cassava root consists of 50% whole protein, and the remaining portion consists of the free amino acids (predominantly glutamic and aspartic acids) and non-protein components such as nitrite, nitrate and cyanogenic compounds. The restricted use of cassava root meal in poultry feed formulation and feeding is due to its low protein content as well as a relative deficiency in essential amino acids [20]. Although high in arginine, glutamic acid and aspartic acid, other amino acids such as methionine, cysteine, phenylalanine, threonine, proline and isoleucine in cassava are low compared to maize [17].…”
Section: Macronutrients Found In Cassava Rootmentioning
confidence: 99%
“…Cassava starch production is a huge and growing industry in the country, with approximately 10 million tonnes of fresh cassava roots used annually (Chauynarong et al, 2009a). Starch extraction also yields cassava pulp as a by-product, which constitutes approximately 30% of the original weight of roots.…”
Section: Introductionmentioning
confidence: 99%
“…Poult. Sci., 9 (4): 203-212, 2015 Starch quantity and quality in cassava is affected by the conditions of the cassava during growing and harvesting (Tonukari, 2004;Chauynarong et al, 2009a). Drought during the early establishment period results in roots with low dry weight and starch content.…”
Section: Introductionmentioning
confidence: 99%